The Economic Impact of UUM International Students’ Expenditure on Business Activities in Changlun - Hassan, Sallahuddin; Othman, Zalila; Sabudin, Noor Sa'adah; Mohd Mohaideen, Zalina; Hidthir, Mohammad Helmi (Association for Social Studies Educa, 2018)
This study examines the potential impact from the expenditure patterns of UUM international students in Changlun on local development particularly among Changlun businesses.For this purpose, the international students’ expenditure patterns in Changlun are examined in terms of the estimated monthly expenditure, the location of spending and the frequency of spending.This study employs the quantitative method to analyze the primary data that were collected from questionnaires distributed to a sample of 150 UUM international students.Among others, the findings of this study empirically reveal that their subsistence spending contributes substantial impacts on Changlun economy leading to continued developments of certain industries; foods and beverages, clothing, telecommunication, and entertainment in the short run.In view of the fact that UUM operations considerably influence the economy of the adjacent town of Changlun, it is recommended that the UUM administrators to strategically plan for increased admission of potential international students to pursue their undergraduate and postgraduate studies at UUM as a means towards continually promoting for intellectual and cultural diversity among UUM students as well as enhancing the economic performance of local businesses.